First record of Archanara neurica (Hübner, 1808) from the Iberian Peninsula (Lepidoptera: Noctuidae) according to DNA barcoding and internal male genitalia - Ortiz, A. S.; Rubio, R. M.; Ranki, T.; Guerrero, J. J.; Yela, J. L. (Zootaxa, 2023)
Archanara neurica (Hübner, 1808) is recorded for the first time from the Iberian Peninsula. The Iberian population represent a link between central European, including French, and Moroccan populations. Male internal genitalia are comparatively described. DNA barcode is presented and compared with those of the other European Archanara, Lenisa and Globia species, formerly considered congeneric. An analysis based on the COI mitochondrial gene provisionally supports the morphologically proposed statement that recognize the three mentioned taxa at the generic level.